A novel homozygous TUB mutation associated with autosomal recessive retinitis pigmentosa in a consanguineous Chinese family - Wei Xu; Ming Xu; Qinqin Yin; Chuangyi Liu; Qiuxiang Cao; Yun Deng; Sulai Liu; Guiyun He (BMC, 2023)
Abstract Background Retinitis pigmentosa (RP) is the most common type of inherited retinopathy. At least 69 genes for RP have been identified. A significant proportion of RP, however, remains genetically unsolved. In this study, the genetic basis of a Chinese consanguineous family with presumed autosomal recessive retinitis pigmentosa (arRP) was investigated. Methods Overall ophthalmic examinations, including funduscopy, decimal best-corrected visual acuity, axial length and electroretinography (ERG) were performed for the family. Genomic DNA from peripheral blood of the proband was subjected to whole exome sequencing. In silico predictions, structural modelling, and minigene assays were conducted to evaluate the pathogenicity of the variant. Results A novel homozygous variant (NM_003320.4: c.1379A > G) in the TUB gene was identified as a candidate pathogenic variant in this parental consanguineous pedigree. This variant co-segregated with the disease in this pedigree and was absent in 118 ethnically matched healthy controls. It's an extremely rare variant that is neither deposited in population databases (1000 Genomes, ExAC, GnomAD, or Exome Variant Server) nor reported in the literature. Phylogenetic analysis indicated that the Asn residue at codon 460 of TUB is highly conserved across diverse species from tropicalis to humans. It was also completely conserved among the TUB, TULP1, TULP2, and TULP3 family proteins. Multiple bioinformatic algorithms predicted that this variant was deleterious. Conclusions A novel missense variant in TUB was identified, which was probably the pathogenic basis for arRP in this consanguineous family. This is the first report of a homozygous missense variant in TUB for RP.